Comparison of different functional EIT approaches to quantify tidal ventilation distribution. (30th January 2018) - Zhao, Zhanqi; Yun, Po-Jen; Kuo, Yen-Liang; Fu, Feng; Dai, Meng; Frerichs, Inez; Möller, Knut
Abstract: Objective : The aim of the study was to examine the pros and cons of different types of functional EIT (fEIT) to quantify tidal ventilation distribution in a clinical setting. Approach : fEIT images were calculated with (1) standard deviation of pixel time curve, (2) regression coefficients of global and local impedance time curves, or (3) mean tidal variations. To characterize temporal heterogeneity of tidal ventilation distribution, another fEIT image of pixel inspiration times is also proposed. Main results : fEIT—regression is very robust to signals with different phase information. When the respiratory signal should be distinguished from the heart-beat related signal, or during high-frequency oscillatory ventilation, fEIT—regression is superior to other types. fEIT—tidal variation is the most stable image type regarding the baseline shift. We recommend using this type of fEIT image for preliminary evaluation of the acquired EIT data. However, all these fEITs would be misleading in their assessment of ventilation distribution in the presence of temporal heterogeneity. Significance : The analysis software provided by the currently available commercial EIT equipment only offers either fEIT of standard deviation or tidal variation. Considering the pros and cons of each fEIT type, we recommend embedding more types into the analysis software to allow the physicians dealing with more complex clinical applications with on-line EIT measurements.